Japanese has syllables: a reply to Labrune*. Issue 1 (15th June 2016) - Kawahara, Shigeto
Abstract : Labrune (2012b) proposes a syllable-less theory of Japanese, suggesting that Japanese has no syllables, with only moras below the foot. She argues that there is no phonetic or psycholinguistic evidence for the existence of syllables in Japanese. This reply summarises and re-examines previous experimental findings that demonstrate that Japanese does show evidence for syllables both phonetically and psycholinguistically. After an extensive review of previous studies, this reply also takes up a number of phonological and theoretical issues that require an explicit response from the perspective of a syllable proponent. On the basis of these considerations, this paper concludes that Japanese does have syllables.